Resiliensi Pelaku Bisnis Kuliner di Masa dan Pasca Pandemi Covid-19 di Kota Makassar - Khomeiny, Mohammad (Emik, 2024)
The Covid-19 epidemic, which began in March 2020, has had an impact on MSMEs worldwide. Most study of Covid-10 looks at the medical aspects of Covid-19 and how people get survived from Covid-19, this article focuses more on resilience of culinary business actors in facing situations during and after the Covid-19 pandemic. This qualitative research was conducted in the metropolitan city of Makassar. Those who participated in this research were seven culinary business actors who are vary on the basis of age, sex, type of business, length of business. Data was collected through the combination of in-depth interview and observation. The results indicate that as a form of resilience during pandemy Covid-19, culinary businesses in Makassar City improving business/financial management, using digital platforms, promotions/advertisements, product innovations and changing service forms. A number of factors that influence the level of online culinary business resilience in Makassar, namely business experience, smaller business scale, their determination to cultural and religious values, open minded in terms of innovation or input and criticism as well as impartial government policies and programs. In order to survive during and after Covid-19 pandemic, culinary business actors apply a specific marketing business strategy.